Biogeochemistry of the rare sulfidic glaciovolcanic cave system on Mount Meager, British Columbia, Canada - Clance, Jared J.; Shaffer, Jacob M. C.; Cable, Morgan L.; Stenner, Christian; Williams-Jones, Glyn; Szynkiewicz, Anna; Paton, Michael; Graham, Kathleen; Vinnes, Olivia; Mikucki, Jill A. (Frontiers in Geochemistry, 2024)
The Mount Meager Volcanic Complex (Q ̓ welq ̓ welústen) is an active glacier-capped volcanic massif in the Garibaldi Volcanic Belt (British Columbia) and the only known glaciovolcanic cave system in North America steadily releasing sulfur-rich gases. In September 2022, leveraging specialized cave explorer expertise, the fumarole-carved ice cave at the Job Glacier on Mt. Meager was surveyed. Direct measurements of fumarolic gas concentrations were taken at the source, with H2S >200 ppm, SO2 >100 ppm, CO2 5200 ppm, and CO 230 ppm. Snowpack and fumarole-associated sediments were characterized for microbial diversity, functional potential, and biogeochemistry including measurements of nutrients, major ions, dissolved organic and inorganic carbon concentrations as well as the stable isotope compositions of carbon, sulfur, hydrogen and oxygen. Green algae (Chlorophyta) dominated the snowpack, consistent with other Pacific Northwest glaciers. Representatives of Firmicutes were the most abundant bacterial sequences detected in our samples, contrasting with other glacier and snowpack samples which harbor abundant Sphingobacteria, Betaproteobacteria, and Alphaproteobacteria. Sediments and water collected inside the cave were mostly high in SO4 2-(5.3-185.2 mg/L) and acidic (3.6-6.0), while most other major anions and cations were below detection of the method used. Snow at the cave entrance had more SO4 2-(0.08 mg/L) and lower pH (5.9) than snow collected at a distance (SO4 2-undetectable, pH 7.6), suggesting influence by fumarole exhalations. Negative δ 13 C values of organic matter (-29.0‰ to -26.1‰, respectively) in sediments suggest in-situ microbial carbon transformations, findings that are supported by the presence of genes encoding complete heterotrophic and autotrophic carbon transformation pathways. The δ 34 S value of H2S was 0‰, suggesting a deep magmatic origin; however, both sulfur-oxidizing and sulfate-reducing microbial phyla were present in the sediment samples as were genes encoding both dissimilatory sulfur-oxidizing and sulfate-reducing pathways. Metagenomic data suggest diverse chemosynthetic lifestyles in the cave microbial community. This study provides insight on the microbiomes associated with a sulfidic glaciovolcanic system and identifies unique analog features for icy celestial bodies like Saturn's moon Enceladus, where cryovolcanic activity may carry biomarkers from the subsurface and deposit them on surface ice.